2014
DOI: 10.4103/0972-124x.134580
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating awareness regarding oral hygiene practices and exploring gender differences among patients attending for oral prophylaxis

Abstract: Background:Oral hygiene is intimated in health of all parts of the body including oral cavity. The understanding of actual practices in keeping the oral heath at standard based on patient's perceptions of oral health care is vital. Understanding the effect of gender on oral health would facilitate the development of successful attitude and behavior modification approach towards sustainable oral health.Purpose of Study:To evaluate awareness regarding oral hygiene practices and exploring gender differences among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 27 publications
(32 reference statements)
3
30
1
Order By: Relevance
“…In our study, 62% females reported higher frequency of brush change within 3 months than males. This finding is similar to a study where females (53.4%) more frequently changing their toothbrush every 3 months in comparison to males (Oberoi et al, 2014). Other demographic variables which presented with higher number of participants changing tooth brush every 3 months are 21 to 30 years age group and higher monthly income group.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, 62% females reported higher frequency of brush change within 3 months than males. This finding is similar to a study where females (53.4%) more frequently changing their toothbrush every 3 months in comparison to males (Oberoi et al, 2014). Other demographic variables which presented with higher number of participants changing tooth brush every 3 months are 21 to 30 years age group and higher monthly income group.…”
Section: Discussionsupporting
confidence: 89%
“…It might also be more difficult to change the behavior of boys than of girls, because girls tend to have more health-directed behavior than boys. [36] The recent study conducted on awareness and use of oral hygiene practices revealed the use of interdental aids was significantly more common among females in comparison to males. [37] For overall medical population it was seen that they had knowledge about what are interdental aids as depicted by higher positive response for items (3-9 and 15-18), but there was inadequate knowledge about the technique of using interdental aids, especially dental floss; and also other interdental aids which are there besides dental floss as depicted by lower positive response for knowledge-based items (10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 98%
“…There is further evidence that girls had reduced access to improved hygienic practices. Nasr et al (2013) comment that boys hand washed more frequently than girls, and Oberoi et al demonstrated that girls less often changed their toothbrush and cited cost as a barrier (Oberoi et al, 2014).…”
Section: (Continued)mentioning
confidence: 99%